Rola wytycznych Centralnego Zarządu Zakładów Karnych w prawie penitencjarnym - Tobis, Aleksander (Wydział Prawa i Administracji UAM, 1982)
Guidelines published under the rule of the Interim Regulations of Imprisonment Sentence Execution of 25 Jan. 1974 are discussed An this article. The guidelines are considered to be intradepartamental by-laws. In connection with the above the following are at issue: counteracting and fighting negative aspects of penitentiary subculture, deviations from the regulations in case of the sentenced women, execution of imprisonment of juvenile delinquents, execution of imprisonment of inadverent offenders, sentenced of burglary, contacts of the sentenced with their relatives. The author presents a classification of guidelines. Their contend; is also discussed in aspect of their formal proclamation, as well as on account of the legislational work on new executive criminal law. Guidelines infringing the right of sentenced to proper execution of their criminal penalty are criticized. The author delimits a scope of possible inclusions of guidelines to the Regulations of the Execution of Imprisonment Sentence which are being created.
The Role of Instructions of Penitentiary Establishments Central Administration in Penitentiary Law